Social–ecological network analysis of governance gaps in a newly designated marine protected area of the Global South - Federico Fraga; Omar Defeo; Ana Inés Borthagaray; Andries Richter (Marine Policy, 2026)

Understanding feedbacks in social–ecological systems using non-recursive structural equation models - Fabio Bozzeda; Omar Defeo (Ecological Modelling, 2026)

On the physical and ecological interpretation of the beach index: a metric-based reformulation - Omar Defeo; Carlos A.M. Barboza; Guilherme Corte; Leonardo Lopes Costa; Eleonora Celentano; Anita de Álava; Anton McLachlan (Estuarine, Coastal and Shelf Science, 2026)

Correction: A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

A thesaurus for improved communication and data integration in sandy beach ecosystem research - Senem Onen Tarantini; Jessica Titocci; Andrea Tarallo; Omar Defeo; Thomas Schlacher; Guilherme Corte; Carlos Alberto de Moura Barboza; Leonardo Lopes Costa; Ivan Franco Rodil; Linda R. Harris; Jeffrey A. Sibaja-Cordero; Martina Pulieri; et al. (Earth Science Informatics, 2026)

Body size scaling across thermal and density gradients in the sandy beach isopod Excirolana braziliensis - Gastón Martínez; Omar Defeo; Matías Arim (Estuarine, Coastal and Shelf Science, 2026)

Connectivity of the Blue Crab Callinectes sapidus in the Southwest Atlantic Ocean: Population Genetics, Biophysical Modeling and Management Implications - Erika Meerhoff; Noemi Rojas‐Hernández; David Véliz; Marcos Alaniz Rodrigues; Vincent Combes; Ricardo Matano; Omar Defeo (Marine Ecology, 2026)
Bio‐oceanographic modeling and population genomics were combined to assess connectivity of the blue crab Callinectes sapidus in the Southwestern Atlantic Ocean, with particular attention to the scale of its fishery management, and the potential role of Marine Protected Areas (MPAs) in Uruguay as larval source zones. A bio‐physical model, coupled with hydrodynamic outputs of a model experiment, incorporated larval vertical migration behavior and key species‐specific traits to simulate dispersal pathways across the region. Population structure was assessed by using SNPs variability. Both approaches revealed substantial connectivity among sampled locations. Genomic population genetic analysis supported a single, well‐mixed population across the study area, consistent with the extensive dispersal predicted by the model. These results highlight the need for management strategies tailored to the species' population structure and emphasize the importance of binational (Brazil‐Uruguay) coordination for this transboundary fishery, which is already showing clear signs of overexploitation. Model simulations further showed that Uruguayan MPAs may act as important larval sources, particularly during winter recruitment under La Niña conditions, exporting propagules to non‐protected areas in southern Brazil. By resolving the spatial and temporal scales of larval exchange, this study enhances regional understanding of connectivity patterns and supports evidence‐based conservation planning for C. sapidus .

Multiscale assessment of anthropogenic impacts on a sandy beach social-ecological system: a mixed-methods approach - Julieta Olalde; Eleonora Celentano; Omar Defeo (Ocean & Coastal Management, 2026)

Towards an ecosystem approach to fisheries in the Galapagos Marine Reserve: A science-driven and adaptive co-management framework - Mauricio Castrejón; Omar Defeo (Marine Policy, 2025)

Seventy years of small-scale fisheries in Uruguay: Trends, challenges, and future directions - Sofía Bausero-Jorcin; Juan A. Licandro; Julio Chocca; Oscar Galli; Enzo Grosso; Cecilia Lezama; Yamandú Marín; Leonardo Ortega; Ignacio Gianelli; Omar Defeo (Ocean & Coastal Management, 2025)

Roles of predator–prey interactions and environmental drivers in sandy beach macrofauna populations - Vitor Figueira Arueira; Pedro Vianna Gatts; Fabio Bozzeda; Marcelo Gomes de Almeida; Carlos Eduardo de Rezende; Ilana Rosental Zalmon; Carlos Alberto de Moura Barboza; Lucia Fanini; Omar Defeo; Leonardo Lopes Costa (Marine Environmental Research, 2025)

Tandem ecosystems: a new perspective on ecological connectivity across the dune-beach interface on sandy shores - Anton McLachlan; Omar Defeo; Patrick A. Hesp (Estuarine, Coastal and Shelf Science, 2025)

Correction: Addressing illegal longlining and ghost fishing in the Galapagos marine reserve: an overview of challenges and potential solutions - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2025)

Correction: Perceptions and attitudes of residents toward small-scale longline tuna fishing in the Galapagos Marine Reserve: conservation and management implications - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2025)

Correction: Commentary: Addressing illegal longlining and ghost fishing in the Galapagos Marine Reserve—a response to Hearn and Bucaram (2025) - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2025)

Beyond “paper parks”: integrating marine fauna into Brazilian protected area management - Helio H. Checon; Beatriz P. Cunha; Yasmina Shah Esmaeili; A. Cecília Z. Amaral; Omar Defeo; Guilherme N. Corte (Ocean & Coastal Management, 2025)

Sandy beaches within meta-social-ecological systems: An integrated framework for ecology, management, and conservation - Omar Defeo; Guilherme Corte; Carlos A.M. Barboza; Paula Debiasi; Leonardo Lopes Costa; Michael Elliott; Lucia Fanini; Linda R. Harris; Nelson Rangel-Buitrago; John Baxter; Alberto Basset; Anton McLachlan (Estuarine, Coastal and Shelf Science, 2025)

Effects of regional oceanography and climate variability on larval connectivity of the wedge clam Donax hanleyanus in South American beaches - Erika Meerhoff; Vincent Combes; Ricardo Matano; Nicolas Barrier; Barbara C. Franco; Alberto R. Piola; Freddy Hernández-Vaca; Omar Defeo (Estuarine, Coastal and Shelf Science, 2025)

Threats and challenges for the conservation of marine molluscs in the southwestern Atlantic - Cristiane Xerez Barroso; Eliane Pintor de Arruda; Florencia Arrighetti; Andrés Averbuj; Gregorio Bigatti; Ramiro Braga; Alvar Carranza; Susete Wambier Christo; Mariana Osório Côrtes; Paulo Márcio Santos Costa; Mariano Cumplido; Omar Defeo; et al. (Aquatic Sciences, 2025)

The role of family in shaping adaptation and adaptive capacity in small-scale fishing communities: The yellow clam fishers in Uruguay - Farah El-Shayeb; Jeremy Pittman; Gabriela Jorge-Romero; Ignacio Gianelli; Omar Defeo (Journal of Rural Studies, 2025)

A 40-year assessment of a harvested sandy beach clam population: Environmental and economic drivers of a regime shift - Fabio Bozzeda; Eleonora Celentano; Leonardo Ortega; Omar Defeo (Ocean & Coastal Management, 2025)

Commentary: Addressing illegal longlining and ghost fishing in the Galapagos Marine Reserve—a response to Hearn and Bucaram (2025) - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2025)

Facing oceanographic, fisheries, and governance hotspots: Scientific evidence and policy implications from the southwest South Atlantic Ocean - Omar Defeo; Bárbara C. Franco; Alberto R. Piola; Claudio C. Buratti; Luis Gustavo Cardoso; Federico Cortés; Ignacio Gianelli; Micaela Giorgini; Gabriela Jorge-Romero; Diego Lercari; Erika Meerhoff; Leonardo Ortega; et al. (Marine Policy, 2025)

The cross-ecosystem dimension of managing sandy beach social-ecological systems - Gabriela Jorge-Romero; Michael Elliott; Omar Defeo (Ocean & Coastal Management, 2025)

Assessing the health and scenic quality of sandy beaches: A large-scale evaluation using expert judgement - Omar Defeo; Juan A. Licandro; Julieta Olalde; Sofía Bausero-Jorcin; Eleonora Celentano; Anita de Álava; Gabriela Jorge-Romero; Diego Lercari; Nelson Rangel-Buitrago (Ocean & Coastal Management, 2024)

An overview of social-ecological impacts of the El Niño-Southern Oscillation and climate change on Galapagos small-scale fisheries - Mauricio Castrejón; Jeremy Pittman; Jorge Ramírez-González; Omar Defeo (Ocean & Coastal Management, 2024)

Rethinking plastic entrapment: Misconceptions and implications for ecosystem services in coastal habitats - Nelson Rangel-Buitrago; Daniel González-Fernández; Omar Defeo; William Neal; Francois Galgani (Marine Pollution Bulletin, 2024)

Environmentally-driven variations in reproductive traits in a sandy beach bivalve throughout its geographic range - Juliana Giménez; Sandra Fiori; María E. Torroglosa; Eleonora Celentano; Arianna Masello; Omar Defeo; Betina J. Lomovasky (Estuarine, Coastal and Shelf Science, 2024)

Addressing illegal longlining and ghost fishing in the Galapagos marine reserve: an overview of challenges and potential solutions - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2024)
Despite regulations aimed at curbing shark finning and bycatch, shark fishing mortality rates continue to escalate, partly due to unintended consequences of these policies which, along with illegal, unreported, and unregulated fishing and ghost fishing, undermine conservation efforts. The ineffectiveness of current regulations to curb shark mortality highlights the pressing need for reevaluating shark conservation strategies, especially in ecologically sensitive areas. In this context, the debate on enforcing longlining bans in multiple-use marine protected areas, including shark sanctuaries, is intensifying. Some argue for total bans to minimize incidental shark mortalities, while others highlight the socioeconomic importance of longlining, advocating for alternative conservation measures. In 2000, longline fishing was banned in the Galapagos Marine Reserve (GMR) as a precautionary measure to prevent illegal fishing of sharks and bycatch of endangered, threatened, and protected species. After 24 years of enforcement, official and anecdotal evidence indicate that illegal small-scale tuna longlining and ghost fishing are increasing threats across the reserve. This paper provides an overview of the longline fishing controversy within the GMR, incorporating scientific evidence, legal and socioeconomic considerations, and perceptions from the Galapagos small-scale fishing community. We offer novel insights and recommendations for the development of the Galapagos small-scale tuna fishery within an ecosystem approach to fisheries. This approach aims to reconcile conservation goals with the needs of local communities, while also proposing innovative solutions to address the longstanding debate surrounding longlining in the GMR.

Blue shark (Prionace glauca) movements, habitat use, and vertical overlap with longline fishing gears in the southwestern Atlantic Ocean - Federico Mas; Enric Cortés; Rui Coelho; Omar Defeo; Philip Miller; John Carlson; Simon Gulak; Andrés Domingo (Marine Biology, 2024)

Assessing the performance of a participatory governance transformation in small-scale fisheries: A case study from Uruguay - Sofía Bausero-Jorcin; Stefan Gelcich; Ignacio Gianelli; Gabriela Jorge-Romero; Cecilia Lezama; Omar Defeo (Marine Policy, 2024)

Global patterns in sandy beach erosion: unraveling the roles of anthropogenic, climatic and morphodynamic factors - Fabio Bozzeda; Leonardo Ortega; Leonardo Lopes Costa; Lucia Fanini; Carlos A. M. Barboza; Anton McLachlan; Omar Defeo (Frontiers in Marine Science, 2023)
Beach erosion is a complex process influenced by multiple factors operating at different spatial scales. Local (e.g., waves, tides, grain size, beach width and coastal development) and regional (e.g., sea level rise and mean sea level pressure) factors both shape erosion processes. A comprehensive understanding of how these drivers collectively impact sandy beach erosion is needed. To address this on a global-scale we assembled a database with in-situ information on key physical variables from 315 sandy beaches covering a wide morphodynamic range and complemented by satellite data on regional variables. Our results revealed the combined influence of local and regional factors on beach erosion rates. Primary drivers were regional anomalies in mean sea level pressure and variations in mean sea level, and local factors such as tide range, beach slope and width, and Dean’s parameter. By analyzing morphodynamic characteristics, we identified five distinct clusters of sandy beaches ranging from wave-dominated microtidal reflective beaches to tide-modified ultradissipative beaches. This energy dissipation gradient emerged as a critical factor, with erosion rates increasing with beach width and dissipativeness. Our study also highlighted the tangible impact of climate change on beach erosion patterns. Hotspots were identified, where intensification of regional anomalies in mean sea level pressure, increasing onshore winds and warming rates, and rising sea levels synergistically accelerated erosion rates. However, local variables were found to either amplify the effects of regional factors on erosion or enhance a beach’s resistance, mitigating erosive trends initiated by regional drivers. Our analysis showed that more than one-fifth of the analyzed beaches are experiencing intense, extreme, or severe erosion rates, and highlighted the significant role of human activities in explaining erosion trends, particularly in microtidal reflective and intermediate beaches. This underscores the long-term threat of coastal squeeze faced by sandy beaches worldwide and emphasizes the need to consider both local and regional drivers in order to understand erosion processes. Integrating localized measurements with broader satellite observations is required for a comprehensive understanding of the main drivers behind coastal evolution, which in turn is needed to manage and preserve these fragile ecosystems that are at risk.

Perceptions and attitudes of residents toward small-scale longline tuna fishing in the Galapagos Marine Reserve: conservation and management implications - Mauricio Castrejón; Omar Defeo (Frontiers in Marine Science, 2023)
Longlining represents a cost-effective fishing modality for catching tuna, but its use is contentious due to the unintended catch of endangered, threatened, and protected (ETP) species. In 2000, longlining was banned in the Galapagos Marine Reserve, Ecuador. Since then, local small-scale fishers have contested this decision. In contrast, longlining ban supporters argue that this regulation is fundamental for conserving ETP species, despite scientific and anecdotal evidence indicating that its effective implementation is unfeasible. We conducted an online survey to investigate Galapagos residents’ perceptions concerning longlining, its ecological impact, and diverse potential management strategies. Our findings revealed misconceptions about longline fishing, which highlight the need for improved public awareness and education regarding longline fishing practices, their impact on ETP species, and possible solutions to this complex social-ecological problem. Our study also highlights Galapagos residents’ openness to find a solution that addresses both fishers’ livelihoods and the conservation of ETP species. Galapagos residents are receptive to implementing evidence-based solutions, including testing new bycatch mitigation methods and more selective fishing gears, enhancing monitoring and enforcement, and creating market-based incentives that encourage progressive and adaptive improvements in fishing practices. To solve the Galapagos longline controversy, we recommend a holistic, adaptive, and evidence-based approach that encourages stakeholders to engage in open dialogue, fosters cross-sector collaboration, and promotes research, communication, and educational initiatives. By raising awareness through comprehensive, rigorous, and unbiased scientific information, this ecosystem-based management approach aims to ensure the sustainable development of the small-scale tuna fishery, while conserving the Galapagos’ invaluable and unique marine biodiversity.

Correction: Sensitivity of fishery resources to climate change in the warm-temperate Southwest Atlantic Ocean - Ignacio Gianelli; Luis Orlando; Luis Gustavo Cardoso; Alvar Carranza; Eleonora Celentano; Patricia Correa; Andrés de la Rosa; Florencia Doño; Manuel Haimovici; Sebastián Horta; Andrés Javier Jaureguizar; Gabriela Jorge-Romero; et al. (Regional Environmental Change, 2023)

Broad-scale benthic habitat classification of the South Atlantic - Kirsty A. McQuaid; Amelia E.H. Bridges; Kerry L. Howell; Tiago B.R. Gandra; Vitor de Souza; Jock C. Currie; Oliver T. Hogg; Tabitha R.R. Pearman; James B. Bell; Lara J. Atkinson; Diane Baum; Jarbas Bonetti; et al. (Progress in Oceanography, 2023)

Sensitivity of fishery resources to climate change in the warm-temperate Southwest Atlantic Ocean - Ignacio Gianelli; Luis Orlando; Luis Gustavo Cardoso; Alvar Carranza; Eleonora Celentano; Patricia Correa; Andrés de la Rosa; Florencia Doño; Manuel Haimovici; Sebastián Horta; Andrés Javier Jaureguizar; Gabriela Jorge-Romero; et al. (Regional Environmental Change, 2023)
Climate change impacts on fishery resources have been widely reported worldwide. Nevertheless, a knowledge gap remains for the warm-temperate Southwest Atlantic Ocean—a global warming hotspot that sustains important industrial and small-scale fisheries. By combining a trait-based framework and long-term landing records, we assessed species’ sensitivity to climate change and potential changes in the distribution of important fishery resources ( n = 28; i.e., bony fishes, chondrichthyans, crustaceans, and mollusks) in Southern Brazil, Uruguay, and the northern shelf of Argentina. Most species showed moderate or high sensitivity, with mollusks (e.g., sedentary bivalves and snails) being the group with the highest sensitivity, followed by chondrichthyans. Bony fishes showed low and moderate sensitivities, while crustacean sensitivities were species-specific. The stock and/or conservation status overall contributed the most to higher sensitivity. Between 1989 and 2019, species with low and moderate sensitivity dominated regional landings, regardless of the jurisdiction analyzed. A considerable fraction of these landings consisted of species scoring high or very high on an indicator for potential to change their current distribution. These results suggest that although the bulk of past landings were from relatively climate-resilient species, future catches and even entire benthic fisheries may be jeopardized because (1) some exploited species showed high or very high sensitivities and (2) the increase in the relative representation of landings in species whose distribution may change. This paper provides novel results and insights relevant for fisheries management from a region where the effects of climate change have been overlooked, and which lacks a coordinated governance system for climate-resilient fisheries.

Reconsidering the longline ban in the Galapagos Marine Reserve - Mauricio Castrejón; Omar Defeo (Marine Policy, 2023)

Where will the children play? A personal perspective on sandy beaches - Anton McLachlan; Omar Defeo (Estuarine, Coastal and Shelf Science, 2023)

Climate change impacts on the atmospheric circulation, ocean, and fisheries in the southwest South Atlantic Ocean: a review - Bárbara C. Franco; Omar Defeo; Alberto R. Piola; Marcelo Barreiro; Hu Yang; Leonardo Ortega; Ignacio Gianelli; Jorge P. Castello; Carolina Vera; Claudio Buratti; Marcelo Pájaro; Luciano P. Pezzi; et al. (Climatic Change, 2020)

Global Observational Needs and Resources for Marine Biodiversity - Gabrielle Canonico; Pier Luigi Buttigieg; Enrique Montes; Frank E. Muller-Karger; Carol Stepien; Dawn Wright; Abigail Benson; Brian Helmuth; Mark Costello; Isabel Sousa-Pinto; Hanieh Saeedi; Jan Newton; et al. (Frontiers in Marine Science, 2019)

Is there a blue transition underway? - Laura Nahuelhual; Omar Defeo; Ximena Vergara; Gustavo Blanco; Sandra L. Marín; Fabio Bozzeda (Fish and Fisheries, 2019)
In this study, we describe what we term a Blue Transition , defined as the passage from fish biomass reduction to recovery in exploited aquatic resources, enabled by aquaculture. A Blue Transition is a key component of emergent “blue” discourses which support that the expansion of aquaculture would relieve pressure on declining capture fisheries, thus contributing to global food security, particularly of the poorest populations. Based on global secondary data and the case of Chile, we explore the evidence of such claim and the implications of a Blue Transition for fisheries and aquaculture development. In 2012, worldwide aquaculture production surpassed wild captures; nevertheless, such turnaround would have not taken place without China's contribution. In Chile, this turnaround occurred in 2014, concurrently with the lowest industrial landings registered since the 1960s (1,227,359 tons). Chile's aquaculture is not relieving wild fisheries or satisfying food demands of the lower income population, in the country or elsewhere. Salmon, the main aquaculture product, is destined mainly to Japan, Russia and United States where, due to its high prices, it is consumed mostly by wealthy consumers. For the case at hand, evidence suggests that a blue transition may be underway but is going in the wrong direction: from what may have been sustainable fisheries management before the 1970s to the overexploited wild fisheries of today.

A social-ecological system framework to assess biological invasions: Corbicula fluminea in Galicia (NW Iberian Peninsula) - Noé Ferreira-Rodríguez; Omar Defeo; Gonzalo Macho; Isabel Pardo (Biological Invasions, 2019)

Inter-specific niche partitioning and overlap in albatrosses and petrels: dietary divergence and the role of fishing discards - Sebastián Jiménez; José C. Xavier; Andrés Domingo; Alejandro Brazeiro; Omar Defeo; Martina Viera; María Inés Lorenzo; Richard A. Phillips (Marine Biology, 2017)

Aggregate patterns of macrofaunal diversity: An interocean comparison - Omar Defeo; Carlos A. M. Barboza; Francisco R. Barboza; William H. Aeberhard; Tatiana M. B. Cabrini; Ricardo S. Cardoso; Leonardo Ortega; Viviane Skinner; Boris Worm (Global Ecology and Biogeography, 2017)
Aim While geographical patterns of species richness are reasonably well explored for single well‐studied taxa, less is known about aggregate patterns of total richness for major biomes and their environmental correlates. Here we analyse continental‐scale aggregate patterns of macrofaunal diversity for sandy beaches, a dominant habitat along the Atlantic and Pacific coasts of South America. Location South American coastlines. Time period Present day (data amassed from studies performed since 1971). Major taxa studied Benthic macrofauna, including crustaceans, polychaetes and molluscs. Methods We compiled richness information for all macrofaunal groups on 263 sandy beaches in South America using standard criteria. We further matched these data with environmental variables including sea surface temperature (SST), chlorophyll a , grain size, beach slope, tide range and various morphometrics. We used generalized linear mixed models to relate environmental factors to observed variation in total macrofaunal richness across all beaches, testing competing hypotheses about environmental correlates and possible drivers of latitudinal diversity. Results Macrofaunal richness decreased from tropical to temperate beaches in the Pacific and followed a parabolic trend in the Atlantic, with the highest biodiversity found at tropical and mid‐latitudinal bands. Beach slope, tidal range and chlorophyll a mostly explained latitudinal trends in macrofaunal richness, followed by grain size, SST and ocean basin. Main conclusions This study indicates that richness of macrofaunal species at a given beach is most closely related to characteristics of the physical habitat, such as beach slope, area and grain size. At this scale, planktonic food supply also appeared to be more important than temperature, which is a dominant explanatory variable of global‐scale variation in species richness.

A decision support tool for response to global change in marine systems: the IMBER ‐ ADA pT Framework - Alida Bundy; Ratana Chuenpagdee; Sarah R Cooley; Omar Defeo; Bernhard Glaeser; Patrice Guillotreau; Moenieba Isaacs; Makino Mitsutaku; R Ian Perry (Fish and Fisheries, 2016)
Global change is occurring now, often with consequences far beyond those anticipated. Although there is a wide range of assessment approaches available to address‐specific aspects of global change, there is currently no framework to identify what governance responses have worked and where, what has facilitated change and what preventative options are possible. To respond to this need, we present an integrated assessment framework that builds on knowledge learned from past experience of responses to global change in marine systems, to enable decision‐makers, researchers, managers and local stakeholders to: (i) make decisions efficiently; (ii) triage and improve their responses; and (iii) evaluate where to most effectively allocate resources to reduce vulnerability and enhance resilience of coastal people. This integrated assessment framework, IMBER ‐ ADA pT is intended to enable and enhance decision‐making through the development, a typology of case‐studies providing lessons on how the natural, social and governance systems respond to the challenges of global change. The typology is developed from a database of case‐studies detailing the systems affected by change, responses to change and, critically, an appraisal of these responses, generating knowledge‐based solutions that can be applied to other comparable situations. Fisheries, which suffer from multiple pressures, are the current focus of the proposed framework, but it could be applied to a wide range of global change issues. IMBER ‐ ADA pT has the potential to contribute to timely, cost‐effective policy and governing decision‐making and response. It offers cross‐scale learning to help ameliorate, and eventually prevent, loss of livelihoods, food sources and habitat.

Co‐management in L atin A merican small‐scale shellfisheries: assessment from long‐term case studies - Omar Defeo; Mauricio Castrejón; Roberto Pérez‐Castañeda; Juan C Castilla; Nicolás L Gutiérrez; Timothy E Essington; Carl Folke (Fish and Fisheries, 2016)
Co‐management (Co‐M), defined as the sharing of management tasks and responsibilities between governments and local users, is emerging as a powerful institutional arrangement to redress fisheries paradigm failures, yet long‐term assessments of its performance are lacking. A comparative analysis of five small‐scale Latin American shellfisheries was conducted to identify factors suggesting success and failure. In Chile, Uruguay and Mexico Co‐M produced positive effects, including stabilization of landings at low levels, increase in abundance, CPUE , unit prices and revenues per unit of effort, and reduced interannual variability in several fishery indicators, particularly in landings. Co‐M was successful because it was mainly bottom‐up implemented and accompanied by‐catch shares (spatial property rights and community quotas). By contrast, Co‐M implementation was unable to prevent the collapse of the Galapagos sea cucumber fishery, as reflected by a decrease in abundance and CPUE . Negative effects were also observed in the Galapagos spiny lobster fishery during Co‐M implementation. However, recovery was observed in recent years, reflected in a stabilization of fishing effort and the highest CPUE and economic revenues observed since the beginning of the Co‐M implementation phase. The combined effects of market forces, climate variability and a moratorium on fishing effort were critical in fishery recovery. We conclude that Co‐M is not a blueprint that can be applied to all shellfisheries to enhance their governability. These social–ecological systems need to be managed by jointly addressing problems related to the resources, their marine environment and the people targeting them, accounting for their socioeconomic and cultural contexts.

Climate‐change impacts on sandy‐beach biota: crossing a line in the sand - David S. Schoeman; Thomas A. Schlacher; Omar Defeo (Global Change Biology, 2014)
Sandy ocean beaches are iconic assets that provide irreplaceable ecosystem services to society. Despite their great socioeconomic importance, beaches as ecosystems are severely under‐represented in the literature on climate‐change ecology. Here, we redress this imbalance by examining whether beach biota have been observed to respond to recent climate change in ways that are consistent with expectations under climate change. We base our assessments on evidence coming from case studies on beach invertebrates in South America and on sea turtles globally. Surprisingly, we find that observational evidence for climate‐change responses in beach biota is more convincing for invertebrates than for highly charismatic turtles. This asymmetry is paradoxical given the better theoretical understanding of the mechanisms by which turtles are likely to respond to changes in climate. Regardless of this disparity, knowledge of the unique attributes of beach systems can complement our detection of climate‐change impacts on sandy‐shore invertebrates to add rigor to studies of climate‐change ecology for sandy beaches. To this end, we combine theory from beach ecology and climate‐change ecology to put forward a suite of predictive hypotheses regarding climate impacts on beaches and to suggest ways that these can be tested. Addressing these hypotheses could significantly advance both beach and climate‐change ecology, thereby progressing understanding of how future climate change will impact coastal ecosystems more generally.

Linking fisheries management and conservation in bioengineering species: the case of South American mussels (Mytilidae) - Alvar Carranza; Omar Defeo; Mike Beck; Juan Carlos Castilla (Reviews in Fish Biology and Fisheries, 2009)

Latitudinal gradients in species richness for South American Mytilidae and Ostreidae: can alternative hypotheses be evaluated by a correlative approach? - Alvar Carranza; Omar Defeo; Juan Carlos Castilla; Thiago Fernando L. V. B. Rangel (Marine Biology, 2009)

Healing small-scale fisheries by facilitating complex socio-ecological systems - Timothy R. McClanahan; Juan Carlos Castilla; Alan T. White; Omar Defeo (Reviews in Fish Biology and Fisheries, 2009)

Reproductive plasticity in mole crabs, Emerita brasiliensis, in sandy beaches with contrasting morphodynamics - Estela Delgado; Omar Defeo (Marine Biology, 2008)

Abundance and orientation responses of the sandhopper Talitrus saltator to beach nourishment and groynes building at San Rossore natural park, Tuscany, Italy - Lucia Fanini; Giovanni Maria Marchetti; Felicita Scapini; Omar Defeo (Marine Biology, 2007)

Tisular and population level responses to habitat harshness in sandy beaches: the reproductive strategy of Donax hanleyanus - Estela Delgado; Omar Defeo (Marine Biology, 2007)

Habitat harshness and morphodynamics: life history traits of the mole crab Emerita brasiliensis in Uruguayan sandy beaches - Eleonora Celentano; Omar Defeo (Marine Biology, 2006)

More than One Bag for the World Fishery Crisis and Keys for Co-management Successes in Selected Artisanal Latin American Shellfisheries - Omar Defeo; Juan Carlos Castilla (Reviews in Fish Biology and Fisheries, 2005)

Latin American benthic shellfisheries: emphasis on co-management and experimental practices - Juan Carlos Castilla; Omar Defeo (Reviews in Fish Biology and Fisheries, 2001)